SYTUACJA AKTORÓW I AKTOREK W RZYMSKIM PRAWIE MAŁŻEŃSKIM - Loska, Elżbieta (Zeszyty Prawnicze, 2016)
THE SITUATION OF ACTORS AND ACTRESSES IN ROMAN MARRIAGE LAW Summary The people of the stage held a very peculiar position in Rome. This was true especially for the women of the theatre. For a long time in ancien Rome actresses fell in the category of feminae probrosae and were treated like other women subject to it. This did not change until the postclassical law when the emperors made it possible for actresses who abandoned their dishonourable profession to clear their name. This option was unavailable to other feminae probrosae. In the late 19th and 20th century the theory of the marital ineligibility of actresses and other feminae probrosae, based on the work of Savigny, was widespread in Romanistic doctrine. Some scholars even spoke of an enforced celibacy. However, it seems that this hypothesis is untenable. The status of actors and actresses in marriage law undoubtedly changed in the course of time. The regulations of the lex Iulia et Papia prohibited actresses from marrying men from the senatorial order, and perhaps all freeborn men. Under the lex Iulia et Papia this kind of union was not regarded as marriage and the couple were treated as unmarried (coelibes); consequently, they did not enjoy the privileges of the married and were subject to penalties. It seems, however, that notwithstanding such prohibitions, once concluded a marriage was treated as legal and valid iure civili. Subsequent emperors made significant changes in this regulation. From the sources preserved it is very hard to conclude how actors were treated by the law. We may safely assume that at least from the time of Augustus’ legislation onwards they could not marry women from the senatorial order. Whether this ban was abolished and if so when, remains a mystery. The Emperor Justinian is known to have permitted ex-actresses and their daughters to marry legally without the need to obtain permission from the emperor. Their position was exceptional – unlike other feminae probrosae they could have their reputation restored and marry persons of the senatorial order, first after gaining the consent of the emperor, later without it. It was a significant difference in relation to the classical law and might have resulted from the personal situation of the Emperor Justinian.